Kommunale eder - Mau, Søren (K&K - Kultur og Klasse, 2018)
In recent years the idea of the commune has occupied an increasingly central place in radical thought as well as practice: ‘the commune’ – “that sphinx so tantalizing to the bourgeois mind”, in Marx’s words – has (again) become a concept around which revolutionary desires condensate and unfold. In this article I explore the concept of the commune in the texts of the contemporary French revolutionary collective The Invisible Committee. I attempt to take their claim that the commune is constituted by an oath seriously, and in order to understand what this means, I draw upon the work of Giorgio Agamben. I also analyse the historical context for the contemporary renaissance of this concept and argue that it should be understood in relation to the crisis of the worker’s movement in the neoliberal epoch as well as contemporary debates about organisation and strategy.